2018
DOI: 10.1021/acsnano.8b01992
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis of Highly Uniform Nickel Multipods with Tunable Aspect Ratio by Microwave Power Control

Abstract: As the importance of anisotropic nanostructures and the role of surfaces continues to rise in applications including catalysis, magneto-optics, and electromagnetic interference shielding, there is a need for efficient and economical synthesis routes for such nanostructures. The article describes the application of cycled microwave power for the rapid synthesis of highly branched pure-phase face-centered cubic crystalline nickel multipod nanostructures with >99% multipod population. By controlling the power del… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 53 publications
0
8
0
Order By: Relevance
“…The authors studied the role of the heating mode, concluding that the particle length is proportional to the duration and number of microwave cycles, whereas the core size is controlled by the continuous MW power delivery. 291 Sun et al synthesized monodisperse Ni NPs via the reduction of Ni(acac) 2 with borane–tributylamine (BTB) complex in a mixture of OAm/OAc. The ligand pair also acted as the solvent medium, while OAc assisted especially the stabilization of the Ni NPs.…”
Section: Monometallic Nanoparticlesmentioning
confidence: 99%
See 1 more Smart Citation
“…The authors studied the role of the heating mode, concluding that the particle length is proportional to the duration and number of microwave cycles, whereas the core size is controlled by the continuous MW power delivery. 291 Sun et al synthesized monodisperse Ni NPs via the reduction of Ni(acac) 2 with borane–tributylamine (BTB) complex in a mixture of OAm/OAc. The ligand pair also acted as the solvent medium, while OAc assisted especially the stabilization of the Ni NPs.…”
Section: Monometallic Nanoparticlesmentioning
confidence: 99%
“…High aspect ratio multipod structures will form under cycled conditions, as depicted in (f). Reprinted with permission from ref 291…”
mentioning
confidence: 99%
“…Therefore, we attempted to synthesize spherical particles by adding the nonpreferentialadsorption type of impurity to the surface of Ni, which could destabilize the nanocrystal facet and strategically tune the shape of the Ni-NPs. 21,22 It is necessary to manipulate selective impurities that can alter the adsorption properties such as the surface energy and surface anisotropy of Ni. We chose sulfur among the various elements that are adsorbed nonpreferentially on the Ni surface and cause a sintering delay effect that can eliminate the defects in MLCCs.…”
Section: Introductionmentioning
confidence: 99%
“…However, the process window is narrow, which inevitably acts as a constraint during the scale-up. Therefore, we attempted to synthesize spherical particles by adding the nonpreferential-adsorption type of impurity to the surface of Ni, which could destabilize the nanocrystal facet and strategically tune the shape of the Ni-NPs. , …”
Section: Introductionmentioning
confidence: 99%
“…Successfully tuning the type and number of stacking faults was first achieved by inducing changes between cubic and hexagonal crystal phases in semiconductor systems, such as InAs, ZnSe, and ZnS nanowires. Because Ni is able to adopt both face-centered cubic ( fcc ) and hexagonal close packed ( hcp ) crystal structures, Ni nanoparticles can have stacking faults. We recently demonstrated that 3D branched Ni nanoparticles made from a mixture of fcc and hcp Ni showed a high activity for the electrocatalytic oxidation of biomass due to high surface area and controlled surface facets . Controlling the amount of hcp – fcc transitions in these 3D branched Ni nanoparticles provides an opportunity to control stacking fault density in a catalytically active metal to enhance catalytic performance.…”
mentioning
confidence: 99%